Ferromagnetic resonance in nanomagnetic metal core and noble metal shell systems - Bala, Tanushree; Enoki, Toshiaki; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
The change in the line widths in the ferromagnetic resonance (FMR) spectra of Co and Ni nanoparticles upon shell formation with noble metals like gold or silver are described. The NicoreAgshell, CocoreAgshell, and CocoreAushell nanoparticles were prepared by a simple transmetallation reaction between the Co and Ni nanoparticles and the Ag+ or AuCl−4 ions. It is revealed that the FMR line width decreases upon Ag shell formation whereas it increases upon core–shell composite formation with Au. Several probable explanations such as the differences in size distributions before and after the reaction or the changes occurring in shape anisotropy of the particles due to the shell formation or the different extents of electronic interaction between the core and shell materials have been offered for this observation.
Keywords: Fmr Study; Line Width Comparison; Magnetic Core-Noble Metal Shell Nanoparticles

Field dependence of the magnetocaloric effect in core-shell nanoparticles - Franco, V.; Conde, A.; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Poddar, P.; Srinath, S.; Phan, M. H.; Srikanth, H. (Journal of Applied Physics, 2010)
The field dependence of the magnetic entropy change peak at the low temperature surface spin freezing transition in chemically synthesized, monodispersed Co, Co-Ag, and Ni-Ag core-shell nanoparticles is studied, with the aim of gaining insight into the critical exponents of this transition. It is evidenced that although the magnitude of the peak entropy change and position of the peak can be tuned by changing the composition and nature (metallic or organic) of the shell and surfactant layers, the characteristics of the spin freezing transition are not altered. The field dependence of the refrigerant capacity also confirms this finding. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3335514]

Foam based synthesis of metal carbonates: establishing the role of spatial confinement for obtaining interesting morphologies - Bala, Tanushree; Sanyal, Ambarish; Pant, Jayashree; Bhagavatula L. V. Prasad (Journal of Computational and Theoretical Nanoscience, 2012)
The crystallization of different carbonates namely lead carbonate, cadmium carbonate and strontium carbonate in aqueous foam stabilized by the surfactant sodium dodecyl sulphate (SDS) by a method of cation entrapment is described. Reaction of ammonium carbonate with the respective cations electrostatically entrapped in the foam results in the formation of minerals, possibly in the Plateau border and Plateau junction regions of the foam. The unusual morphology of the crystals obtained from foam based synthetic method as compared to the crystals prepared in aqueous solution shows the utility of the template for the growth of crystals with an unusual morphology due to constrained environment. The materials are well characterized using TEM, SEM, EDAX and FTIR techniques. The large interfacial area of the liquid lamellae in the foam provides a striking possibility for the large-scale synthesis for not only minerals but also other nanoscale materials.

Fine control of nanoparticle sizes and size distributions: temperature and ligand effects on the digestive ripening process - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Nanoscale, 2013)
It is demonstrated that a fine control over the size and size distribution of nanoparticles could be achieved using digestive ripening at different temperatures. Such variations in size and size distributions hugely influence the self-assembled processes in nanoparticles, and result in superlattice structures that are controlled by subtle interplay between ligand orientational entropy and their interdigitation and the van der Waals attraction between the metal cores.